Typological and factor analysis of personality in the context of architectural design - Bolharova, Natalia (Art and Design, 2026)
Contemporary development of architecture and design is characterised by a growing demand for environments that consider not only functional and aesthetic aspects but also the psychological characteristics of users. The relevance of the study lies in the need to integrate individual psychological traits into design solutions to ensure comprehensive human comfort. The purpose of the study was to develop a methodological approach to create a personalised architectural environment based on the Big Five model, which allows correlating personality traits with specific spatial, colouristic, material, and lighting parameters. The study employed methods of scientific literature analysis, logical-semantic comparison, generalisation, case analysis, and visualisation of results. Eight leading personality theories were examined and subjected to comparative analysis in terms of their applicability to design practice. Tables were developed to demonstrate the correspondence between psychological characteristics and design solutions, particularly the influence of the Big Five traits on the choice of spatial layouts, colour palettes, materials, and lighting scenarios. Examples were created to illustrate the adaptation of interiors and public spaces to user profiles with varying levels of openness to experience, extraversion, agreeableness, conscientiousness, and neuroticism. The results confirmed that a personalised approach enhances emotional comfort, productivity, and psychological well-being, while also ensuring a balance between individual and collective needs. The practical value of the study lies in the development of a system of recommendations for architects and designers, aimed at shaping individually comfortable, flexible, and psychologically balanced environments in residential, office, and urban architecture